Processes in Auroral Oval and Outer Electron Radiation Belt - Stepanova, M (Springer Berlin Heidelberg, 2018)
We have analyzed the role of auroral processes in the formation of the outer radiation belt, considering that the main part of the auroral oval maps to the outer part of the ring current, instead of the plasma sheet as is commonly postulated. In this approach, the outer ring current is the region where transverse magnetospheric currents close inside the magnetosphere. Specifically, we analyzed the role of magnetospheric substorms in the appearance of relativistic electrons in the outer radiation belt. We present experimental evidence that the presence of substorms during a geomagnetic storm recovery phase is, in fact, very important for the appearance of a new radiation belt during this phase. We discuss the possible role of adiabatic acceleration of relativistic electrons during storm recovery phase and show that this mechanism may accelerate the relativistic electrons by more than one order of magnitude. © 2018, The Author(s).
Keywords: Magnetospheric storm and substorm; Auroral oval; Acceleration of electrons of the outer electron radiation belt